Alternative dispute resolution in environmental and natural resource disputes: national and international perspectives - Ansari, Abdul Haseeb; Ahmad, Muhamad Hassan; Omoola, Sodiq Olalekan (Indian Law Institute, 2017)
Resolving environmental disputes, wherever necessary, by ADR mechanisms is of numerous advantages, especially since they resolve disputes amicably and in the interest of all, including conservation of the environment, the compliance level of the reached dispute resolutions is quite high in comparison to those resolved on the basis of the contentious method of dispute resolution. It is for this reason that efforts are being made at countries like New Zealand, India, Australia and international level, to resolve environmental disputes through the use of ADR mechanisms. But the scenario of their applicability is not yet appreciably high. The paper discusses the level of applications of the ADR mechanisms at both the levels and suggests that: at state level, efforts should be made to maximise the use of the ADR mechanisms; and at international level, an international environmental court should be created under the auspices of the United Nations to resolve such disputes primarily by application of ADR mechanisms, and exceptionally by contentious means. In order to facilitate this, a comprehensive legal framework should be worked out.